Grammatical Errors on EFL Students’ Final Project Writings - Zewitra; Poppy Fauziah (Jurnal Bahasa Inggris Terapan, 2020)
Making errors is an unavoidable part of learning a new language, especially for those who do not use that new language as their first medium of communication. Writing in a foreign language can be a considerably tough challenge for EFL learners, one of the problems is regarding the grammatical rules. This present study attempts to discover and analyze the grammatical errors found in EFL students’ final project writing. It employed a descriptive qualitative method using a textual analysis process by adopting the theory of Dulay et al regarding grammatical error analysis. (Dulay et al., 1982) classify grammatical errors into four; omission, addition, misformation, and misordering. Five students’ final projects with a total number of 2884 sentences became the object of this research. The final projects were taken from Politeknik Negeri Bandung (Polban) English Department graduates of 2018 and they were limited to the project of ‘Travel Writing’ only. Travel Writing was chosen due to the fact that it contains more various types of sentences, more complicated sentence structure, and higher level of language modification. The results of this study claim that all types of grammatical errors presented by Dulay et al are found in those five students’ final projects. Misformation is the most frequent error the students made in producing their travel writing products by 74% (380 out of 516 errors) while misordering is the least one by 1% (7 out of 516 errors). Theoretically, the findings can be a base for the next researchers to further analyze the cause of this error production. Meanwhile, practically the results can be used by curriculum makers as a guide to evaluate and develop new curriculum, syllabus, materials, and teaching methods which are more suitable for EFL students in order to communicate effectively and write skillfully. Keywords: error analysis, grammatical error, writing, travel writing